Attending to Attention: A Systematic Review of Attention and Reading - Sarah M.R. Eisensmith; Premela G Deck; Melissa R Jenkins; April Harris Britt; Kirsten Kainz; David Ansong (International Journal of School Social Work, 2022)
Background: Extensive research has conclusively linked inattention to poor reading performance. The process by which this relation occurs remains somewhat undefined, which makes it difficult for practitioners to identify key intervention targets. Objectives: This systematic review will synthesize current peer-reviewed research on the developmental relationship between inattention and reading. The primary aim of this review was to describe how inattention negatively relates to the development of literacy from preschool through middle childhood. A secondary aim of this review was to summarize recent research on the potential differential relationship between attention and literacy among students overrepresented in ratings of inattention, including boys and students of color. Design and Methods: PsycInfo, Education Full Text, ERIC, and ProQuest Education, and Dissertations and Theses were searched, using a broad search string. The initial search resulted in 1,262 potentially relevant studies published since the most recent authorization of the Every Child Succeeds Act (i.e., from December 2015-2019) for review. Out of 1,262 citations found, 70 empirical studies were screened and assessed for eligibility, and 16 met the specific inclusion criteria. A coding sheet was then used to synthesize data from the included studies. Results: Among preschool and elementary school children, inattention, whether measured through observer ratings or performance tasks, has a consistent, negative impact on reading skills as reported both by teachers, standardized instruments, and classroom performance outcomes. Results point to multiple pathways through which inattention may have a negative impact on reading outcomes. Evidence points to a negative and direct effect of inattention on the development of and performance in reading concurrently and over time. Inattention may have an additional, indirect, and negative effect on reading performance through its negative impact on early literacy and cognitive skills, including phonological awareness and processing, vocabulary, and working memory. There is a lack of research on potential differential processes by which attention relates to reading among subgroups of children who are at elevated risk for poor literacy outcomes. Conclusions and Implications: Assessing for and intervening in early attention problems in preschool and kindergarten is essential to promote optimal reading outcomes for all students. There is an urgent need for future research to investigate potential differential processes in the relation between attention and reading performance for children who are at an elevated risk for reading problems. School social workers are especially prepared and located to address the interaction of child and classroom factors within schools that impede student performance in early grades and set up challenges for later success.
Keywords: attention problems; reading development; early intervention; differential process